Diastolic blood pressure predicts enlarged vertebral venous plexus and intracranial pressure in patients with bilateral transverse sinus stenosis - Min Li; Min Li; Xiaogang Gao; Fengwei Liu; Jingkun Sun; Ning Xia; Ran Meng; Ran Meng; Xunming Ji; Xunming Ji (Frontiers in Neurology, 2022)
BackgroundBilateral transverse sinus stenosis (BTSS) is associated with intracranial hypertension. Enlarged vertebral venous plexus (EVVP) refers to a compensation mechanism against elevated intracranial pressure (ICP) in patients with BTSS. This study aims to investigate the influencing factors of EVVP.MethodsPatients with BTSS were prospectively recruited from the neurology department and neurosurgery department of Xuanwu Hospital Capital Medical University from January 2020 to December 2021.ResultsA total of 37 patients were enrolled with a mean age of 45.42 ± 15.64 years. Women tend to be more susceptible to BTSS. The most common co-morbid disease was hypertension. The most common clinical manifestations were visual disorders, headaches, and tinnitus. BMI and DBP were significantly higher in BTSS patients without EVVP than those with EVVP. Multivariate analysis revealed that diastolic blood pressure (DBP) was negatively correlated with EVVP. In addition, a positive correlation between DBP and the ICP was also observed. A DBP of 81.5 mmHg was calculated as the cutoff value for the presence of EVVP. BTSS patients with DBP ≤ 81.5 mmHg had a higher incidence of EVVP and a lower ICP compared to those with DBP > 81.5 mmHg.ConclusionsDBP was identified as an independent predictor of EVVP. DBP was lower (≤81.5 mmHg) in patients with EVVP and therefore was associated with a lower ICP in patients with BTSS.